KHALÄªFAH DAN KHILAFÄ€H MENURUT ALQURAN - Rahim, Abd. (State Institute of Islamic Studies (IAIN) Palu, 2012)
Abstract: The first problem which came up when Rasulullah Muhammad saw. passed away is the problem of khilafah/leadership, which concerned with the right figure for the position of the head/chairman of the state. Islamic does not provide a patented system of leadership and administration for the moslem. This is not difficult to understand, since the system is not only a guarantee which can create a benefit and prosperity of ummah, but also as something which may change as the age development. Whereas the goal of nation building is to create and realize prosperity. Therefore, the goal of nation or the realization of prosperity and welfare is by applying the universal principles of Islamic teachings, namelyÂ the principle of justice in law enforcement, principle of amanah in carrying ou the duty, responsibility and professionalism.Â Â Kata Â Kunci: khalÄ«fah, khilÄfah, sistem kepemimpinan,Â Alquran